A Decomposition of Korean Sovereign Bond Yields: Joint Estimation Using Sovereign CDS and Bond Data1. (8th January 2015) - Kim, Jungmu; Lee, Changjun
Abstract: We suggest a methodology to decompose sovereign bond yields into four components (risk‐free, default risk, risk premium, and non‐default) using both sovereign credit default swaps and bond data. Applying the methodology to one of the largest emerging markets, Korea, we find that each fraction varies over time and across bonds. In addition, the default risk accounts for only a small fraction of sovereign yield spreads, and a substantial portion is attributable to risk premium and non‐default components. In particular, the risk premium is substantially time‐varying; moreover, it increases in order to account for a major portion of the heightened yield spread during a financial crisis, implying that global investors prefer to hold safer assets. Therefore, higher risk premiums per unit risk are required than before. Our findings provide evidence on both flight‐to‐quality and time‐varying risk premium.